2011
DOI: 10.1111/j.1600-0625.2011.01360.x
|View full text |Cite
|
Sign up to set email alerts
|

Inducible nitric oxide synthase (iNOS) and α-melanocyte-stimulating hormones of iNOS origin play important roles in the allergic reactions of atopic dermatitis in mice

Abstract: To elucidate the possible involvement of nitric oxide (NO) derived from inducible NO synthase (iNOS) in the pathogenesis of patients with allergic rhinitis, we used an animal model of atopic dermatitis (AD) induced by epicutaneous sensitization and analysed the differences in ear thickness, the frequency of scratching and plasma levels of ovalbumin-specific immunoglobulin E (OVA-IgE), transforming growth factor (TGF)-β, tumor necrosis factor (TNF)-α, adrenocorticotropic hormone (ACTH) and α-melanocyte-stimulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
35
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 37 publications
1
35
0
Order By: Relevance
“…In mouse models of AD-like lesions, skin showed increased iNOS expression and serum samples were noted to have increased nitrites compared to controls (14). Additionally, even after epicutaneous sensitization, iNOS knockout mice do not show the normally-induced symptoms of swelling/scratching, nor increased nitrite levels, as control mice show (15). More specifically to AD in humans, serum nitrate levels were found to be elevated in pediatric atopic dermatitis patients and were related to both severity of disease as well as eosinophil count (16).…”
Section: Discussionmentioning
confidence: 97%
“…In mouse models of AD-like lesions, skin showed increased iNOS expression and serum samples were noted to have increased nitrites compared to controls (14). Additionally, even after epicutaneous sensitization, iNOS knockout mice do not show the normally-induced symptoms of swelling/scratching, nor increased nitrite levels, as control mice show (15). More specifically to AD in humans, serum nitrate levels were found to be elevated in pediatric atopic dermatitis patients and were related to both severity of disease as well as eosinophil count (16).…”
Section: Discussionmentioning
confidence: 97%
“…In addition, the flavonoids quercetin and kaempferol show anti-inflammatory effects by modulating the pro-inflammatory factors, such as inducible nitric oxide synthase (iNOS) and cyclooxygenase-2 (COX-2) (García-Mediavilla et al, 2007). Nitric oxide (NO) derived from inducible NO synthase (iNOS) is involved in the pathogenesis of allergic rhinitis and exacerbation of atopic dermatitis symptoms like scratching (Orita et al, 2011). Thus, it is concluded that consuming the aqueous extract of field dodder seeds can be helpful for the improvement of AD lesions due to decrease of inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Imai et al describe increased blood histamine levels in transgenic mice spontaneously developing long-lasting dermatitis (by skin-specific IL-33 expression) [27], a phenotype which resembles the chronic phase of atopic dermatitis. Other groups could show elevated histamine levels in skin or serum only after repeated epicutaneous challenge [28], [29], suggesting that re-exposure might be necessary to induce measurable increases in histamine levels. It is thus conceivable that repeated patching could also lead to histamine increases in our model, a read-out parameter we did not address, though.…”
Section: Discussionmentioning
confidence: 99%